2012
DOI: 10.3390/app2020453
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Based Superhydrophobic Coatings

Abstract: Superhydrophobic coatings, inspired by nature, are an emerging technology. These water repellent coatings can be used as solutions for corrosion, biofouling and even water and air drag reduction applications. In this work, synthesis of monodispersive silica nanoparticles of ~120 nm diameter has been realized via Stöber process and further functionalized using fluoroalkylsilane (FAS-17) molecules to incorporate the fluorinated groups with the silica nanoparticles in an ethanolic solution. The synthesized fluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(124 citation statements)
references
References 43 publications
3
119
0
2
Order By: Relevance
“…(3). Brassard et al [38] previously showed with a model that the fluorinated silica nanoparticles also follows the Cassie-Baxter model [31]. They have shown the roughness of the silica nanoparticle films is proportional to the air fraction and that water contact angle increases with the increase of the roughness of the films due to the increase of the silica nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3). Brassard et al [38] previously showed with a model that the fluorinated silica nanoparticles also follows the Cassie-Baxter model [31]. They have shown the roughness of the silica nanoparticle films is proportional to the air fraction and that water contact angle increases with the increase of the roughness of the films due to the increase of the silica nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The manufacturer of the RTV silicone specified that it contains mainly three different molecules: trimethoxymethylsilane, hexamethyldisilazane and octamethylcyclotetrasiloxane. The peaks at 800 and 1100 cm −1 correspond to the asymmetric stretching vibration of Si-O-Si group [38] and [42]. A peak approximately at −1 is due to the Si-O-C bond.…”
Section: (C) and (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches have been used to modify the surfaces of PDMS, including: chemical methods [9][10][11] and physical methods, such as ultraviolet ozone [12], and oxygen plasma [8,13]. In this paper, we used molding in order to reach the required roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of fluorine atoms to bioactive molecules enhance and improve their pharmacological properties [16][17][18]. Also, presence of hetero-atoms increased membrane, permeability, which enhances the electrostatic force and hydrophobic binding stability against metabolic transformations [18][19][20][21][22]. As part of the interested research program in the fluorine substituted heterocyclic nitrogen systems as biocidal agents [23][24][25][26][27], the present work tends to synthesize, some new fluorinated-thiobarbituric acids full fused in view of their anti-HIV and cyclin-dependent kinase 2.…”
Section: Introductionmentioning
confidence: 99%